NCDs and Climate Change: Shared Opportunities for Action - Husain, Marium (International Journal of Human and Health Sciences (IJHHS), 2024)
NCDs and climate change are linked. As climate change continues to impact our local and global communities, we see more direct and indirect impacts on NCDs: food security and nutrition, respiratory diseases and air pollution, infectious diseases, access to healthcare services, and much more. Please join us for an informative discussion on a topic that affects all humanity. International Journal of Human and Health Sciences Supplementary Issue 01: 2024 Page: S9